Elevated Carbon Monoxide to Carbon Dioxide Ratio in the Exhaled Breath of Mice Treated With a Single Dose of Lipopolysaccharide. (18th September 2014) - Langeroudi, Arash Ghalyanchi; Hirsch, Charlotte M.; Estabragh, Azadeh Shojaee; Meinardi, Simone; Blake, Donald R.; Barbour, Alan G.
Abstract : By gas chromatographic analysis, the ratio of carbon monoxide to carbon dioxide increased in exhaled breath of 2 mouse strains injected with different doses of Escherichia coli lipopolysaccharide. The ratios correlated with inflammation biomarkers and heme oxygenase-1 expression in blood. Abstract : Background.  Analysis of volatile organic chemicals in breath holds promise for noninvasive diagnosis and monitoring of patients, but investigation of this in experimental mouse models has been limited. Of particular interest is endogenous production of carbon monoxide as a biomarker of inflammation and, more particularly, during sepsis. Methods.  Using a nose-only collection procedure for unanesthetized individual adult mice and sensitive gas chromatography of carbon monoxide (CO) and carbon dioxide (CO2 ) of sampled breath, we investigated the responses of mice to one-time injections with different doses of purified Escherichia coli lipopolysaccharide. Two strains of mice were examined: BALB/c and C3H, including an endotoxin-resistant mutant (HeJ) as well as the wild type (HOuJ). Results.  The CO to CO2 ratio increased in a dose-responsive manner within hours in treated BALC/c mice but not control mice. The CO/CO2 values declined to the range of control mice within 48–72 h after the injection of lipopolysaccharide. Breath CO/CO2 values correlated with systemic inflammation biomarkers in serum and heme oxygenase-1 gene expression in blood. C3H/HOuJ mice, but not the HeJ mice, had similar increases of the CO/CO2 ratio in response to the endotoxin. Conclusions.  Carbon monoxide concentrations in exhaled breath of at least 2 strains of mice increase in response to single injections of endotoxin. The magnitude of increase was similar to what was observed with a bacteremia model. These findings with an experimental model provide a rationale for further studies of normalized CO concentrations in human breath as an informative biomarker for staging and monitoring of sepsis.